Entomofauna da lentilha. I - Percevejos pentatomidae (Hemiptera) - Link, Dionisio (Revista do Centro de Ciências Rurais, 2008)
Foi determinada a ocorrência e freqüência de percevejos pentatomídeos sobre lentilha e estudou-se os hábitos de oviposição de Piezodorus guildinii (Westwood, 1837). Quatro espécies de pentatomídeos foram coletadas, sendo Acrosternum armigera (Stal, 1859) e Dichelops furcatus (Fabricius,1775) novas constatações. A espécie mais freqüente e abundante foi P. guildinii. O número médio de ovos por postura de P. guildinii foi de 13,15, variando de 2 a 29. Houve referência para ovipositar nas partes superiores externas da planta de lentilha. A maioria das posturas (47,5%) foi parasitada por Telenomus mormideae Lima, 1935 (Hymenoptera: Scelionidae).AbstractA search was made to determine the occurrence and abundance of stink bugs on lentils. The oviposition of Piezodorus guildinii (Westwood, 1937) on lentil plants was also studied. Four species of pentatomids were captured, Acrosternum armigera (Stal, 1859) and Dichelops furcatus (Fabricius, 1775) were new. P. guildinii was the most frequent and abundant pentatomid. The mean number of eggs per mass from 202 egg masses was 13.15, and the number of eggs per mass was between 2 and 29. The P. guildinii female prefers to oviposite on the upper side of the lentil plant. Telenomus mormideae Lima, 1935 (Hymenoptera: Scelionidae) parasitized the eggs of 47.5% of the egg masses.